2014
DOI: 10.1111/1758-2229.12136
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a key Hg methylation gene, hgcA, in wetland soils

Abstract: The corrinoid protein, HgcA has been shown to be essential for Hg methylation in anaerobic bacteria. We investigated the diversity of hgcA from temperate and tropical wetland soils where Hg methylation is demonstrated. Sequences obtained from both environments clustered with those from the δ-Proteobacteria, Chloroflexi and Methanomicrobia with significant overlap in hgcA phylogeny between libraries. Clear differences in hgcA distribution were observed between two highly contrasting sites within a tropical wetl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
88
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 28 publications
4
88
0
Order By: Relevance
“…Primers for qPCR were chosen based on the literature, notably for their capacity to amplify a large section of the biodiversity of targeted genes ( Table 2, Table S1). Nevertheless, primers for hgcA are known to amplify better the hgcA sequences from the δ-Proteobacteria over more diverse families such as firmicutes (Schaefer et al 2014). This was done in order to target reliably previously characterized Hg methylators, e.g., Desulfovibrio and Geobacter species.…”
Section: Rna Extraction and Reverse Transcriptase Quantitative Polymementioning
confidence: 99%
See 1 more Smart Citation
“…Primers for qPCR were chosen based on the literature, notably for their capacity to amplify a large section of the biodiversity of targeted genes ( Table 2, Table S1). Nevertheless, primers for hgcA are known to amplify better the hgcA sequences from the δ-Proteobacteria over more diverse families such as firmicutes (Schaefer et al 2014). This was done in order to target reliably previously characterized Hg methylators, e.g., Desulfovibrio and Geobacter species.…”
Section: Rna Extraction and Reverse Transcriptase Quantitative Polymementioning
confidence: 99%
“…The specific mechanisms and metabolic pathways involved in Hg methylation remains undefined, but two genes in particular (cluster hgcA and hgcB) have been shown to be required for Hg methylation (Gilmour et al 2013;Parks et al 2013). The diversity of these genes was recently investigated in sites with distinct methylation potentials, namely the everglades, wetlands, and rice paddies (Bae et al 2014;Liu et al 2014;Schaefer et al 2014). Nonetheless, our global understanding of the biotically mediated Hg methylation, and the quantitative importance of such processes, notably hgcAB cluster activity at the ecosystem level is only emerging and remains insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, any organism whose genome contains homologs of hgcA and hgcB was predicted to be capable of Hg methylation. Microorganisms from diverse origins and environments containing homologs of both hgcA and hgcB have been identified (11,(19)(20)(21). All cultured microbes assayed thus far that possess hgcA and hgcB methylate Hg, whereas all microbes assayed that lack homologs of hgcA and hgcB are unable to methylate Hg (11).…”
mentioning
confidence: 99%
“…Considerable recent research has been devoted to the identification of the complex geochemical interactions that control the availability of Hg 2ϩ for uptake by methylating prokaryotes (6, 7); however, limited work has been conducted to identify the dominant phylogenetic groups responsible for methylation in the Everglades (8). Specific knowledge of the dominant mercury methylators would provide valuable information on their physiologies and ecologies, thereby providing additional insight into the specific controls on mercury methylation in this ecosystem.…”
mentioning
confidence: 99%
“…Specific knowledge of the dominant mercury methylators would provide valuable information on their physiologies and ecologies, thereby providing additional insight into the specific controls on mercury methylation in this ecosystem. The dominant methylators of mercury in the Everglades are generally considered to be sulfate-reducing prokaryotes (SuRP) (9), although recent work indicated that diverse groups of prokaryotes may also contribute to mercury methylation in other anaerobic environments (10,11) and in low-sulfate regions of the Everglades (8). In addition, it should be noted that not all SuRP are capable of mercury methylation, nor are all mercury-methylating SuRP equally efficient at methylating mercury (11,12).…”
mentioning
confidence: 99%